Advanced Functional Materials 2020
DOI: 10.5772/intechopen.93368
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials for Drug Delivery: Sources, Classification, Synthesis, Processing, and Applications

Abstract: A way to avoid or minimize the side effect that could result in drug delivery to cells with increased efficiency and performance in the health rehabilitation process is to use biocompatible and biodegradable drug carriers. These are essentially biomaterials that are metallic, ceramic, or polymeric in nature. The sources of these materials must be biological in its entire ramification. The classification, synthesis, processing, and the applications to which these materials are put are the essential components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 133 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…Firstly, the nanocarriers can be used to release the cargos by activating them. Secondly, the polymer of the charged surface can be positive to get internalized by the cells that are targeted [ 65 ]. Table 8 lists the various polymers used in the development of controlled release drug delivery systems (CRDDS).…”
Section: Concept Of Biomaterials In Controlled Drug Deliverymentioning
confidence: 99%
“…Firstly, the nanocarriers can be used to release the cargos by activating them. Secondly, the polymer of the charged surface can be positive to get internalized by the cells that are targeted [ 65 ]. Table 8 lists the various polymers used in the development of controlled release drug delivery systems (CRDDS).…”
Section: Concept Of Biomaterials In Controlled Drug Deliverymentioning
confidence: 99%
“…Similarly, an investigative study of high molecular weight chitosan in wound healing showed exceptionally good re-epithelialization and fast wound closure compared to fucidin-ointment treated wounds [13]. Collagen and gelatin nanofibrous scaffolds are fabricated for wound healing and cartilaginous tissue regeneration respectively [15,16] and nanofibrous scaffolds of hyaluronic acid mimics the ECM essential in controlling cellular function [2,17].…”
Section: Biomaterials and Wound Healingmentioning
confidence: 99%
“…Margaret O. Ilomuanya 1 *, Ibilola M. Cardoso-Daodu 1 , Uloma N. Ubani-Ukoma 1 and Adannaya C. Adebona 2…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the field of pharmacology, electrospun nanofibers have generated significant interest thanks to biofunctional systems. They allow a direct interaction between polymers and drugs, and for this reason, it is of paramount importance to find a polymer that is compatible with the drug and that both materials are biocompatible [ 15 ].…”
Section: Introductionmentioning
confidence: 99%